Information Location Of Elementary School With Certified Teachers At Lampung Province Based Android - Arfida, Septilia; -, Amnah; Wibowo, Hariyanto (Prosiding International conference on Information Technology and Business (ICITB), 2017)
The development of information technology is currently going very fast. Information at any time can be accessed quickly and accurately becomes very important. One device that can access information quickly is an Android smart phone. Specific information in education for elementary school is a manifestation of teacher quality in improving national education in Indonesia. So the information in the world of education is a vehicle to actualize all the potential that exists. One of the information needed is to know the location of public elementary school that have certified teacher in Lampung Province. Information based Android is a picture of the location of public elementary schools that have certified teachers. This Android Based Application is expected to provide information on the location of public elementary schools on the data collection of teachers who have been certified in Lampung Province. So that can be monitored and known by the Education Office of Bandar Lampung, but it also provides information to other parties in need it. Keywords: Location Of Public Elementary School, Certified Teacher, and Android.